Advantageous Role of Ir0 Supported on TiO2 Nanosheets in Photocatalytic CO2 Reduction to CH4: Fast Electron Transfer and Rich Surface Hydroxyl Groups - Tang, Kunlin; Wang, Zhiqiang; Zou, Weixin; Guo, Hongyu; Wu, Yuchao; Pu, Yu; Tong, Qing; Wan, Haiqin; Gu, Xianrui; Dong, Lin; Rong, Junfeng; Chen, Yu-Wen (ACS applied materials & interfaces, 2021)
Ir-based heterogeneous catalysts for photocatalytic CO2 reduction have rarely been reported and are worthy of investigation. In this work, TiO2 nanosheets with a higher specific surface area and more oxygen vacancies were employed to support Ir metal by impregnation (Imp) and ethylene glycol (EG) reduction methods. In comparison with Ir/TiO2 (Imp) and TiO2, Ir/TiO2 (EG) exhibited excellent photocatalytic performance toward CO2 reduction, especially for CH4 production on account of the oxygen defect of TiO2 and rich surface hydroxyl groups produced from the interaction between TiO2 nanosheets and metallic Ir. In situ ESR suggested that the oxygen defect was significant for CO2 adsorption/activation. Furthermore, metallic Ir was beneficial for photogenerated electron transfer, surface hydroxyl generation, and adsorption of the CO intermediate, generating more available electrons and reducing agents for CH4 production. In situ CO2 DRIFTS confirmed the key synergistic interaction between the oxygen defect and metallic Ir in the photoreduction from CO2 to CH4.